2009
DOI: 10.1161/strokeaha.108.532960
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Outcome of Carotid Atheromatous Disease in Patients With Stroke in Pakistan

Abstract: Background and Purpose-Limited data exist on the frequency and outcome of carotid artery disease in Pakistan. Such information would help guide the usefulness of screening for the condition in this low-middle income health care setting. Methods-A prospective, descriptive study was conducted among 3 large teaching hospitals in Karachi, Pakistan. Patients referred for carotid Doppler ultrasound examination were included if they had experienced a stroke or TIA within the previous month. The severity and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
6
17
0
Order By: Relevance
“…Almost 80% had normal studies; only 3% had >70% symptomatic carotid stenosis. These findings support previous reports of a low prevalence of carotid artery disease in Asia [23]. However, intracranial disease was common with 9% of MRAs showing focal occlusion and 24% showing focal stenosis of a large vessel.…”
Section: Discussionsupporting
confidence: 91%
“…Almost 80% had normal studies; only 3% had >70% symptomatic carotid stenosis. These findings support previous reports of a low prevalence of carotid artery disease in Asia [23]. However, intracranial disease was common with 9% of MRAs showing focal occlusion and 24% showing focal stenosis of a large vessel.…”
Section: Discussionsupporting
confidence: 91%
“…Recent systematic review and metaregression analysis of 40 studies showed 4.2% (95% CI, 3.1-5.7%) pooled prevalence of moderate stenosis; with advancing age prevalence was increasing and men were affected more often than women [15] . A recently published three-center study in Pakistan, which used a similar methodology as ours, reported a frequency of carotid disease in the same order as we found in Egypt [16] , taking into consideration that Pakistan is a transitional country like Egypt.…”
Section: Discussionsupporting
confidence: 78%
“…Lack of stroke awareness, poor access to resources, financial constraints and presentation to the hospital outside the thrombolytic window limit tPa usage [57]. From 2005 to 2007, only 18 out of 1,185 stroke patients received tPa at an academic medical center in Pakistan.…”
Section: Resultsmentioning
confidence: 99%